Jumanji Extremism? How games and gamification could facilitate radicalization processes - Linda Schlegel (Journal for Deradicalization, 2020)
While the last years have seen increased engagement with gaming in relation to extremist attacks, its potential role in facilitating radicalization has received less attention than other factors. This article makes an exploratory contribution to the theoretical foundations of the study of gaming in radicalization research. It is argued that both top-down and bottom up gamification have already impacted extremist discourse and potentially radicalization processes but that research on gamification in other contexts points to a much wider application of gamification to extremist propaganda distribution tools in the future. The potential influence of video games on radicalization processes exceeds the transfer of the popular argument that exposure to violent media leads to desensitization to the context of radicalization and includes the exploitation of pop culture references, increases in self-efficacy regarding violence, and the direct experience of retropian visions through the content of games.